2010
DOI: 10.1348/014466609x468411
|View full text |Cite
|
Sign up to set email alerts
|

Cultural stereotypes of disabled and non‐disabled men and women: Consensus for global category representations and diagnostic domains

Abstract: Despite the fact that disabled people comprise a heterogeneous social group, cross-impairment cultural stereotypes reflect a consistent set of beliefs used to characterize this population as dependent, incompetent, and asexual. Using a free-response methodology, stereotypical beliefs about disabled men (DM) and women (DW) were contrasted against the stereotypes of their non-disabled counterparts illustrating the dimensions considered most diagnostic of each group. Results revealed that both disabled and non-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 35 publications
5
81
0
7
Order By: Relevance
“…Devine, 1989). This emphasis on societal beliefs is commonly used when measuring stereotypes (e.g., see Devine, 1989;Fiske et al, 2002;Nario-Redmond, 2010), and helps to reduce social desirability concerns.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Devine, 1989). This emphasis on societal beliefs is commonly used when measuring stereotypes (e.g., see Devine, 1989;Fiske et al, 2002;Nario-Redmond, 2010), and helps to reduce social desirability concerns.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Studies examining stereotypes of disabled people in general indicate a predominantly negative stereotype. For example, Nario-Redmond (2010) found that disabled men and women were characterised as dependent, incompetent, and asexual. Fiske, Cuddy, Glick, and Xu (2002) similarly found that disabled people were seen as low in competence, though high in warmth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, and for generations, bodily differences have determined social structures based on this distinction 8,9 . In this way, a "model of humanity" has been developed, to which the first fit and the others do not.…”
mentioning
confidence: 99%
“…In this way, a "model of humanity" has been developed, to which the first fit and the others do not. In turn, this distinction is a reflection of the fact that, when we think of disability, we usually think of it in terms of a sociological category 9 and not as a condition that we can experience.…”
mentioning
confidence: 99%